2012
DOI: 10.1039/c2ra20142a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of ionic liquids in separation science and mass spectrometry

Abstract: Ionic liquids (ILs) have drawn considerable interest for their use in various analytical techniques including chromatography, extractions, and mass spectrometry. This is largely due to the flexibility in tuning the physicochemical properties of ILs. There has been a significant increase in the number of publications over the last decade in which ILs have been employed as a chromatographic stationary phase, extraction solvent, or sorbent material in various preconcentration techniques. This review article highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(85 citation statements)
references
References 215 publications
3
81
0
1
Order By: Relevance
“…26). It has also been widely used as an electrolyte, with a wide electrochemical window 28 . Previous related attempts to slow DNA translocation speeds used glycerol, which has a low conductivity and limited the approach to a narrow viscosity window (1.2-5 cP) 29 .…”
Section: Viscosity Gradient System In Mos 2 Nanoporesmentioning
confidence: 99%
“…26). It has also been widely used as an electrolyte, with a wide electrochemical window 28 . Previous related attempts to slow DNA translocation speeds used glycerol, which has a low conductivity and limited the approach to a narrow viscosity window (1.2-5 cP) 29 .…”
Section: Viscosity Gradient System In Mos 2 Nanoporesmentioning
confidence: 99%
“…Ionic liquids, which are salts that are liquid below 100˚C [1], show great potential [1][2][3] as environmentallyfriendly extraction solvents due to their unique properties, such as negligible vapour pressure, high thermal stability, non-flammability [4]. More specifically, hydrophobic ionic liquids may be used for the separation of metal ions from aqueous solutions and wastewaters, where they can be specifically designed to act as extractors themselves [5] or, more commonly, serve as an extraction medium for active materials, such as crown ethers [6,7] or any other ion-specific extractants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it had been reported that only several strong solvents can dissolve cellulose. Recently, it has been reported that an ionic liquid can dissolve cellulose [125,126]; ionic liquids have unique properties such as low vapor pressure, non-flammability, high ion conductivity, and the ability to dissolve various materials. If strong solvents are used to dissolve cellulose, it is difficult to prepare enzyme-immobilized membrane by using cellulose because of solvent-induced damage to the enzyme.…”
Section: Chemically-stable Materials For the Matrixmentioning
confidence: 99%